An end-to-end model framework for understanding and predicting changes in Antarctic marine ecosystems - Ilari Stollberg; Sophie Bestley; Andrew Constable; Elizabeth A. Fulton; Javier Porobic; David Green; Denise O’Sullivan; Mao Mori; Stuart Corney; Michael Sumner; Jessica Melbourne-Thomas (Ecological Modelling, 2026)

First detection and tracing of grapevine red blotch virus (GRBV) in Australia using tiled amplicon sequencing - Tonny Kinene; Andrew S. Taylor; Richard Fennessy; Brenda A. Coutts; David Lovelock; Cuiping Wang; Kamalpreet Kaur; Thao Tran; Brendan Rodoni; Fiona E. Constable; Monica A. Kehoe (Archives of Virology, 2025)
Grapevine red blotch virus (GRBV; species Grablovirus vitis , genus Grablovirus , family Geminiviridae ) poses a significant threat to viticulture worldwide, impacting grapevine health and wine quality. Here, we report the first detection and tracing of GRBV in Australia and provide a summary of a subsequent survey to determine the extent of GRBV distribution in Western Australia. Additionally, the study introduces a tiled amplicon sequencing method, which, when combined with long-read nanopore sequencing, enables rapid GRBV genome sequencing. Our analysis suggests a single introduction of GRBV from North America to Australia through the state of Victoria and subsequently to Western Australia. Finally, this study provides insight into the epidemiology of GRBV, based on strain variation and distribution, which is a crucial step in supporting an emergency biosecurity response and implementing effective control measures to safeguard the sustainability of the wine industry in Australia.

Insights into the last 100 ky of geomagnetic field variability using numerical dynamo simulations - Stephen J. Mason; Christopher J. Davies; Andrew T. Clarke; Catherine G. Constable (Earth and Planetary Science Letters, 2024)

Imperatives for integrated science and policy in managing greenhouse gas risks to the Southern Polar Region - Andrew J. Constable (Global Change Biology, 2022)

Warming world, changing ocean: mitigation and adaptation to support resilient marine systems - Rowan Trebilco; Aysha Fleming; Alistair J. Hobday; Jess Melbourne-Thomas; Amelie Meyer; Jan McDonald; Phillipa C. McCormack; Kelli Anderson; Narissa Bax; Stuart P. Corney; Leo X. C. Dutra; Hannah E. Fogarty; et al. (Reviews in Fish Biology and Fisheries, 2022)

A Decade of Incorporating Social Sciences in the Integrated Marine Biosphere Research Project (IMBeR): Much Done, Much to Do? - Ingrid van Putten; Rachel Kelly; Rachel D. Cavanagh; Eugene J. Murphy; Annette Breckwoldt; Stephanie Brodie; Christopher Cvitanovic; Mark Dickey-Collas; Lisa Maddison; Jess Melbourne-Thomas; Haritz Arrizabalaga; Kumiko Azetsu-Scott; et al. (Frontiers in Marine Science, 2021)
Successful management and mitigation of marine challenges depends on cooperation and knowledge sharing which often occurs across culturally diverse geographic regions. Global ocean science collaboration is therefore essential for developing global solutions. Building effective global research networks that can enable collaboration also need to ensure inter- and transdisciplinary research approaches to tackle complex marine socio-ecological challenges. To understand the contribution of interdisciplinary global research networks to solving these complex challenges, we use the Integrated Marine Biosphere Research (IMBeR) project as a case study. We investigated the diversity and characteristics of 1,827 scientists from 11 global regions who were attendees at different IMBeR global science engagement opportunities since 2009. We also determined the role of social science engagement in natural science based regional programmes (using key informants) and identified the potential for enhanced collaboration in the future. Event attendees were predominantly from western Europe, North America, and East Asia. But overall, in the global network, there was growing participation by females, students and early career researchers, and social scientists, thus assisting in moving toward interdisciplinarity in IMBeR research. The mainly natural science oriented regional programmes showed mixed success in engaging and collaborating with social scientists. This was mostly attributed to the largely natural science (i.e., biological, physical) goals and agendas of the programmes, and the lack of institutional support and push to initiate connections with social science. Recognising that social science research may not be relevant to all the aims and activities of all regional programmes, all researchers however, recognised the (potential) benefits of interdisciplinarity, which included broadening scientists’ understanding and perspectives, developing connections and interlinkages, and making science more useful. Pathways to achieve progress in regional programmes fell into four groups: specific funding, events to come together, within-programme-reflections, and social science champions. Future research programmes should have a strategic plan to be truly interdisciplinary, engaging natural and social sciences, as well as aiding early career professionals to actively engage in such programmes.

Responses of Southern Ocean Seafloor Habitats and Communities to Global and Local Drivers of Change - Madeleine J. Brasier; David Barnes; Narissa Bax; Angelika Brandt; Anne B. Christianson; Andrew J. Constable; Rachel Downey; Blanca Figuerola; Huw Griffiths; Julian Gutt; Susanne Lockhart; Simon A. Morley; et al. (Frontiers in Marine Science, 2021)
Knowledge of life on the Southern Ocean seafloor has substantially grown since the beginning of this century with increasing ship-based surveys and regular monitoring sites, new technologies and greatly enhanced data sharing. However, seafloor habitats and their communities exhibit high spatial variability and heterogeneity that challenges the way in which we assess the state of the Southern Ocean benthos on larger scales. The Antarctic shelf is rich in diversity compared with deeper water areas, important for storing carbon (“blue carbon”) and provides habitat for commercial fish species. In this paper, we focus on the seafloor habitats of the Antarctic shelf, which are vulnerable to drivers of change including increasing ocean temperatures, iceberg scour, sea ice melt, ocean acidification, fishing pressures, pollution and non-indigenous species. Some of the most vulnerable areas include the West Antarctic Peninsula, which is experiencing rapid regional warming and increased iceberg-scouring, subantarctic islands and tourist destinations where human activities and environmental conditions increase the potential for the establishment of non-indigenous species and active fishing areas around South Georgia, Heard and MacDonald Islands. Vulnerable species include those in areas of regional warming with low thermal tolerance, calcifying species susceptible to increasing ocean acidity as well as slow-growing habitat-forming species that can be damaged by fishing gears e.g., sponges, bryozoan, and coral species. Management regimes can protect seafloor habitats and key species from fishing activities; some areas will need more protection than others, accounting for specific traits that make species vulnerable, slow growing and long-lived species, restricted locations with optimum physiological conditions and available food, and restricted distributions of rare species. Ecosystem-based management practices and long-term, highly protected areas may be the most effective tools in the preservation of vulnerable seafloor habitats. Here, we focus on outlining seafloor responses to drivers of change observed to date and projections for the future. We discuss the need for action to preserve seafloor habitats under climate change, fishing pressures and other anthropogenic impacts.

Stakeholder Engagement in Decision Making and Pathways of Influence for Southern Ocean Ecosystem Services - Josh Solomonsz; Jess Melbourne-Thomas; Andrew Constable; Rowan Trebilco; Ingrid van Putten; Lyn Goldsworthy (Frontiers in Marine Science, 2021)
Southern Ocean ecosystem management is characterized by a unique and complex international network of stakeholders and stakeholder relationships (a ‘transactional landscape’) relating to the globally significant services that these ecosystems support. This transactional landscape spans governments, industry (fishing and tourism), scientific research, conservation non-government organizations, civil society, and international decision-making forums. We used a network approach for stakeholder mapping to provide the first description of the transactional landscape for Southern Ocean ecosystem management – both in terms of the connections between stakeholders and ecosystem services, and directly between stakeholder groups. We considered 65 stakeholders and their relationships to 12 provisioning, regulating, supporting and cultural ecosystem services. An analysis of the connections within this network reveals differences in the degree of connectivity between stakeholders and ecosystem services. Notably, ecosystem science facilitates high connectivity between stakeholders and provisioning services, but there is little connectivity between stakeholders and supporting services. We then applied a formal ‘values-rules-knowledge’ framework to a set of case studies to analyze the decision-making process in relation to Southern Ocean ecosystem services, as well as the relative importance of different stakeholder groups which were considered in the network analysis. Our analyses suggest that emphases for decision making have been on knowledge and rules, but that wider consideration of values across the broader stakeholder landscape – together with science (knowledge) and governance (rules) – might better support decision making for Southern Ocean ecosystem conservation and management, and provide a stronger foundation for sustainable provision of ecosystem services into the future.

Combating ecosystem collapse from the tropics to the Antarctic - Dana M. Bergstrom; Barbara C. Wienecke; John van den Hoff; Lesley Hughes; David B. Lindenmayer; Tracy D. Ainsworth; Christopher M. Baker; Lucie Bland; David M. J. S. Bowman; Shaun T. Brooks; Josep G. Canadell; Andrew J. Constable; et al. (Global Change Biology, 2021)
Globally, collapse of ecosystems—potentially irreversible change to ecosystem structure, composition and function—imperils biodiversity, human health and well‐being. We examine the current state and recent trajectories of 19 ecosystems, spanning 58° of latitude across 7.7 M km 2 , from Australia's coral reefs to terrestrial Antarctica. Pressures from global climate change and regional human impacts, occurring as chronic ‘presses’ and/or acute ‘pulses’, drive ecosystem collapse. Ecosystem responses to 5–17 pressures were categorised as four collapse profiles—abrupt, smooth, stepped and fluctuating. The manifestation of widespread ecosystem collapse is a stark warning of the necessity to take action. We present a three‐step assessment and management framework (3As Pathway Awareness , Anticipation and Action ) to aid strategic and effective mitigation to alleviate further degradation to help secure our future.

Global Drivers on Southern Ocean Ecosystems: Changing Physical Environments and Anthropogenic Pressures in an Earth System - Simon A. Morley; Doris Abele; David K. A. Barnes; César A. Cárdenas; Cedric Cotté; Julian Gutt; Sian F. Henley; Juan Höfer; Kevin A. Hughes; Stephanie M. Martin; Carlos Moffat; Marilyn Raphael; et al. (Frontiers in Marine Science, 2020)
The manuscript assesses the current and expected future global drivers of Southern Ocean (SO) ecosystems. Atmospheric ozone depletion over the Antarctic since the 1970s, has been a key driver, resulting in springtime cooling of the stratosphere and intensification of the polar vortex, increasing the frequency of positive phases of the Southern Annular Mode (SAM). This increases warm air-flow over the East Pacific sector (Western Antarctic Peninsula) and cold air flow over the West Pacific sector. SAM as well as El Niño Southern Oscillation events also affect the Amundsen Sea Low leading to either positive or negative sea ice anomalies in the west and east Pacific sectors, respectively. The strengthening of westerly winds is also linked to shoaling of deep warmer water onto the continental shelves, particularly in the East Pacific and Atlantic sectors. Air and ocean warming has led to changes in the cryosphere, with glacial and ice sheet melting in both sectors, opening up new ice free areas to biological productivity, but increasing seafloor disturbance by icebergs. The increased melting is correlated with a salinity decrease particularly in the surface 100 m. Such processes could increase the availability of iron, which is currently limiting primary production over much of the SO. Increasing CO 2 is one of the most important SO anthropogenic drivers and is likely to affect marine ecosystems in the coming decades. While levels of many pollutants are lower than elsewhere, persistent organic pollutants (POPs) and plastics have been detected in the SO, with concentrations likely enhanced by migratory species. With increased marine traffic and weakening of ocean barriers the risk of the establishment of non-indigenous species is increased. The continued recovery of the ozone hole creates uncertainty over the reversal in sea ice trends, especially in the light of the abrupt transition from record high to record low Antarctic sea ice extent since spring 2016. The current rate of change in physical and anthropogenic drivers is certain to impact the Marine Ecosystem Assessment of the Southern Ocean (MEASO) region in the near future and will have a wide range of impacts across the marine ecosystem.

Delivering Sustained, Coordinated, and Integrated Observations of the Southern Ocean for Global Impact - Louise Newman; Petra Heil; Rowan Trebilco; Katsuro Katsumata; Andrew Constable; Esmee van Wijk; Karen Assmann; Joana Beja; Phillippa Bricher; Richard Coleman; Daniel Costa; Steve Diggs; et al. (Frontiers in Marine Science, 2019)

Using stable isotope data to advance marine food web modelling - Stacey A. McCormack; Rowan Trebilco; Jessica Melbourne-Thomas; Julia L. Blanchard; Elizabeth A. Fulton; Andrew Constable (Reviews in Fish Biology and Fisheries, 2019)

Outcomes from 10 years of biodiversity offsetting - Philip Gibbons; Andrew Macintosh; Amy Louise Constable; Kiichiro Hayashi (Global Change Biology, 2018)
We quantified net changes to the area and quality of native vegetation after the introduction of biodiversity offsetting in New South Wales, Australia—a policy intended to “prevent broad‐scale clearing of native vegetation unless it improves or maintains environmental values.” Over 10 years, a total of 21,928 ha of native vegetation was approved for clearing under this policy and 83,459 ha was established as biodiversity offsets. We estimated that no net loss in the area of native vegetation under this policy will not occur for 146 years. This is because 82% of the total area offset was obtained by averting losses to existing native vegetation and the rate that these averted losses accrue was over‐estimated in the policy. There were predicted net gains in 10 of the 14 attributes used to assess the quality of habitat. An overall net gain in the quality of habitat was assessed under this policy by substituting habitat attributes that are difficult to restore (e.g. mature trees) with habitat attributes for which restoration is relatively easy (e.g. tree seedlings). Long‐term rates of annual deforestation did not significantly change across the study area after biodiversity offsetting was introduced. Overall, the policy examined here provides no net loss of biodiversity: (i) many generations into the future, which is not consistent with intergenerational equity; and (ii) by substituting different habitat attributes, so gains are not equivalent to losses. We recommend a number of changes to biodiversity offsetting policy to overcome these issues.

A Synergistic Approach for Evaluating Climate Model Output for Ecological Applications - Rachel D. Cavanagh; Eugene J. Murphy; Thomas J. Bracegirdle; John Turner; Cheryl A. Knowland; Stuart P. Corney; Walker O. Smith; Claire M. Waluda; Nadine M. Johnston; Richard G. J. Bellerby; Andrew J. Constable; Daniel P. Costa; et al. (Frontiers in Marine Science, 2017)

Object ownership and action: the influence of social context and choice on the physical manipulation of personal property - Merryn D. Constable; Ada Kritikos; Ottmar V. Lipp; Andrew P. Bayliss (Experimental Brain Research, 2014)

Climate change and Southern Ocean ecosystems I: how changes in physical habitats directly affect marine biota - Andrew J. Constable; Jessica Melbourne‐Thomas; Stuart P. Corney; Kevin R. Arrigo; Christophe Barbraud; David K. A. Barnes; Nathaniel L. Bindoff; Philip W. Boyd; Angelika Brandt; Daniel P. Costa; Andrew T. Davidson; Hugh W. Ducklow; et al. (Global Change Biology, 2014)
Antarctic and Southern Ocean ( ASO ) marine ecosystems have been changing for at least the last 30 years, including in response to increasing ocean temperatures and changes in the extent and seasonality of sea ice; the magnitude and direction of these changes differ between regions around Antarctica that could see populations of the same species changing differently in different regions. This article reviews current and expected changes in ASO physical habitats in response to climate change. It then reviews how these changes may impact the autecology of marine biota of this polar region: microbes, zooplankton, salps, Antarctic krill, fish, cephalopods, marine mammals, seabirds, and benthos. The general prognosis for ASO marine habitats is for an overall warming and freshening, strengthening of westerly winds, with a potential pole‐ward movement of those winds and the frontal systems, and an increase in ocean eddy activity. Many habitat parameters will have regionally specific changes, particularly relating to sea ice characteristics and seasonal dynamics. Lower trophic levels are expected to move south as the ocean conditions in which they are currently found move pole‐ward. For Antarctic krill and finfish, the latitudinal breadth of their range will depend on their tolerance of warming oceans and changes to productivity. Ocean acidification is a concern not only for calcifying organisms but also for crustaceans such as Antarctic krill; it is also likely to be the most important change in benthic habitats over the coming century. For marine mammals and birds, the expected changes primarily relate to their flexibility in moving to alternative locations for food and the energetic cost of longer or more complex foraging trips for those that are bound to breeding colonies. Few species are sufficiently well studied to make comprehensive species‐specific vulnerability assessments possible. Priorities for future work are discussed.

Lessons from CCAMLR on the implementation of the ecosystem approach to managing fisheries - Andrew J. Constable (Fish and Fisheries, 2011)
The Commission for the Conservation of Antarctic Marine Living Resources (CCAMLR) is widely recognized as a leading international organization in developing best practice in the ecosystem approach to managing fisheries. CCAMLR provides a useful case study for examining the impediments to implementing ecosystem‐based fisheries management (EBFM) because it has EBFM principles embedded within its convention rather than having to make a transition from single‐species management to an ecosystem approach. CCAMLR is demonstrating that (i) EBFM does not need to equate to complexity in management and (ii) methods can be developed to decide on spatial management strategies for fisheries so that predators of target species are not disproportionately affected as a result of spatial and/or temporal dependencies of predators on their prey. Science has an important role in implementing EBFM, not only in measuring and assessing the status of target species and their predators but also in designing cost‐effective management strategies and in resolving disputes. Importantly, attention needs to be given to developing the capability and tools to overcome differences amongst scientists in providing advice to managers. The CCAMLR experience suggests that, without adequate safeguards, voluntary participation by fishing States in CCAMLR and its consensus environment do not provide strong foundations for achieving, in the long term, the ecosystem‐based principles for managing fisheries when there is any degree of scientific uncertainty. Some solutions to these issues are discussed. Overall, broader‐than‐CCAMLR solutions amongst the international community as well as the continued commitment of CCAMLR Members will be required to resolve these issues.